CONSTRUCTING MINDFULNESS-BASED WRITING INSTRUCTION IN GLOCALIZED LANGUAGE EDUCATION: A STUDY ON STUDENTS’ WRITING ABILITY - Vike Aprilianin Marwintaria Saputri (Vol. 2 No. 1 (2024): Proceeding of International Conference on Cultures & Language 2024, 2024)
Writing as an academic task is considered the hardest part of English instruction and learning. Communicative skills in writing can be taught by using one strategy that is mindful learning. The purpose of this study was to provide insights into the effectiveness of mindfulness-based writing instruction in enhancing students' writing ability within the framework of glocalized language education. The study was carried out from January to April 2024 at the Jinarakkhita Buddhist College of Lampung. The population of the research was the second-semester Buddhist Communication Science Department students in the academic year 2023-2024. In this study, the researcher attempts to incorporate mindfulness into the writing process. The researcher used a rubric score to analyse and measure the students’ writing ability before and after treatment. The data were collected by administering essay writing to assess students’ writing ability. The result showed that an increase in the in the pre-test and post-test average score from 48.5 to 62. There is a significant difference in writing competency between the students who are taught by using a mindfulness-based writing instruction and the students who were taught by using conventional writing strategy. The finding showed descriptively that the students who were taught by using mindfulness-based writing instruction achieved better writing comprehension. In conclusion, the second semester students’ writing abilities have improved as a result of the use of mindfulness-based writing instruction as they are more expressive and creative in conducting the idea. Besides that, mindfulness-based writing instruction emphasizing self-awareness and presence during the writing process. It can improve productivity, mental well-being, collaboration and learning for students.